PHENOTYPIC AND GENOTYPIC CHARACTERISATION OF WILD AND CULTURE CICHLID POPULATIONS (Sarotherodon melanotheron) IN LAGOS STATE, NIGERIA. - USMAN, A. B; AGBEBI, O. T; OGUNTADE, O. R; ODULATE, D O; UMOH, I. A; UKENYE, E. A.; OKETOKI, T (Nigerian Journal of Fisheries, 2017)
This study was carried out to characterize and identify Sarotherodon melanotheron using morphometric and molecular approach. A total of forty (40) samples were collected; 10 samples each of farm-raised (Akinsateru and NIOMR farms, Lagos) and wild (Lagos and Badagry Lagoon, Lagos) were collected in Lagos State for 3 months. The standard lengths and weights of the fish used for the study ranged from 8.40 cm to 17.20 cm; 26.10g to 133.00g for farm-raised and wild populations respectively .Seventeen morphometric and meristic characters were measured with divider, thread, measuring board and ruler. Data collected were analyzed using t-Test. The results showed there were significant differences (p≤0.05) among the characters measured in wild and farm-raised S. melanotheron. Random amplified polymerase DNA (RAPD-PCR) analysis was carried out using Operon primers (OPC 04, 05, 10, OPR 02 and OPI 05).Of the 5 primers, only 4 primers showed both stable amplification and polymorphism except on some samples (both wild and culture) having low reproducibility. The bands generated from the molecular results showed that the inter-specific similarity coefficient between the wild was 78%; culture was 80%; and 100% for both wild and culture samples.